2018
DOI: 10.13045/jar.2018.00255
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Domestic and Foreign Clinical Research on Ultrasound-Guided Acupuncture

Abstract: Background: The purpose of this study was to analyze domestic and foreign clinical research into ultrasoundguided Oriental medicine acupuncture. Methods: Ultrasound-guided Oriental medicine acupuncture studies were retrieved from PubMed, CNKI, KISS, NDSL, and OASIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
(1 reference statement)
0
1
0
1
Order By: Relevance
“…국내 한의계에서 초음파를 활용한 임상 연구는 도플러 초 음파를 활용한 장인수 등의 연구가 1996년 처음 보고되었으 며, 이후 2009년을 기점으로 크게 증가하였다 15,16) . 2018년 김 보현 등이 초음파 유도하 자침에 대해 발표한 체계적 문헌고찰 연구에서는 초음파 진단기기를 활용하여 침도(Acupotomy), 호침(Acupunctrue), 약침(Pharmacopuncture), 전침(Electroacupuncture) 등 다양한 중재법을 초음파 가이드하 시술 에 활용한 사례가 확인되었다 17) . 한의계에서 안전한 자침 시술, 침 시술의 정확도 제고를 위 해 한의학연구원과 원광대학교 한의과대학 경혈학교실 연구진 은 한의사용 자화침 트래킹 가이드 초음파 Acuviz (Fcu Co. Daejeon, Korea)의 개발에 참여하였으며 '고위험부위 초음파 유도하 자침 가이드북'을 출간하였다 18) .…”
Section: Introduction Introductionunclassified
“…국내 한의계에서 초음파를 활용한 임상 연구는 도플러 초 음파를 활용한 장인수 등의 연구가 1996년 처음 보고되었으 며, 이후 2009년을 기점으로 크게 증가하였다 15,16) . 2018년 김 보현 등이 초음파 유도하 자침에 대해 발표한 체계적 문헌고찰 연구에서는 초음파 진단기기를 활용하여 침도(Acupotomy), 호침(Acupunctrue), 약침(Pharmacopuncture), 전침(Electroacupuncture) 등 다양한 중재법을 초음파 가이드하 시술 에 활용한 사례가 확인되었다 17) . 한의계에서 안전한 자침 시술, 침 시술의 정확도 제고를 위 해 한의학연구원과 원광대학교 한의과대학 경혈학교실 연구진 은 한의사용 자화침 트래킹 가이드 초음파 Acuviz (Fcu Co. Daejeon, Korea)의 개발에 참여하였으며 '고위험부위 초음파 유도하 자침 가이드북'을 출간하였다 18) .…”
Section: Introduction Introductionunclassified
“…Kim et al [2] reported that ultrasound-guided acupuncture, pharmacopuncture and acupotomy has been used to accurately identify the anatomical structures of the treatment regions, and enhance the accuracy of the procedure. It was also reported that ultrasound equipment was used to avoid the adverse effects of acupuncture procedures, such as pneumothorax.…”
Section: Introductionmentioning
confidence: 99%